Planning Production and Inventories in the Extended Enterprise A State-of-the-Art Handbook, Volume 2 - Kempf, Karl G.; Keskinocak, Pinar; Uzsoy, Reha.; SpringerLink (New York, NY Springer New York, 2011)
In two volumes, Planning Production and Inventories in the Extended Enterprise: A State of the Art Handbook examines production planning across the extended enterprise against a backdrop of important gaps between theory and practice. The early chapters describe the multifaceted nature of production planning problems and reveal many of the core complexities. The middle chapters describe recent research on theoretical techniques to manage these complexities. Accounts of production planning system currently in use in various industries are included in the later chapters. Throughout the two volumes there are suggestions on promising directions for future work focused on closing the gaps. Included in Volume 1 are papers on the Historical Foundations of Manufacturing Planning and Control; Advanced Planning and Scheduling Systems; Sustainable Product Development and Manufacturing; Uncertainty and Production Planning; Demand Forecasting; Production Capacity; Data in Production and Supply Chain Planning; Financial Uncertainty in SC Models; Field Based Research in Production Control; Collaborative SCM; Sequencing and Coordination in Outsourcing and Subcontracting Operations; Inventory Management; Pricing, Variety and Inventory Decisions for Substitutable Items; Perishable and Aging Inventories; Optimization Models of Production Planning Problems; Aggregate Modeling of Manufacturing Systems; Robust Stability Analysis of Decentralized Supply Chains; Simulation in Production Planning; and Simulation-Optimization in Support of Tactical and Strategic Enterprise Decisions. Included in Volume 2 are papers on Workload and Lead-Time Considerations under Uncertainty; Production Planning and Scheduling; Production Planning Effects on Dynamic Behavior of A Simple Supply Chain; Supply and Demand in Assemble-to-Order Supply Chains; Quantitative Risk Assessment in Supply Chains; A Practical Multi-Echelon Inventory Model with Semiconductor Application; Supplier Managed Inventory for Custom Items with Long Lead Times; Decentralized Supply Chain Formation; A Cooperative Game Approach to Procurement Network Formation; Flexible SC Contracts with Options; Build-to-Order Meets Global Sourcing for the Auto Industry; Practical Modeling in Automotive Production; Discrete Event Simulation Models; Diagnosing and Tuning a Statistical Forecasting System; Enterprise-Wide SC Planning in Semiconductor and Package Operations; Production Planning in Plastics; SC Execution Using Predictive Control; Production Scheduling in The Pharmaceutical Industry; Computerized Scheduling for Continuous Casting in Steelmaking; and Multi-Model Production Planning and Scheduling in an Industrial Environment.
Chapter 1. Production Planning Under Uncertainty with Workload Dependent Lead-Times: Lagrangean Bounds and Heuristics -- Chapter 2. Production Planning and Scheduling: Interaction and Coordination -- Chapter 3. The Effects of Production Planning on the Dynamic Behavior of a Simple Supply Chain: An Experimental Study -- Chapter 4. Supply and Demand Synchronization in Assemble-to-Order Supply Chains -- Chapter 5. Quantitative Risk Assessment in Supply Chains: A Case Study Based on Engineering Risk Analysis Concepts -- Chapter 6. A Practical Multi-Echelon Inventory Model with Semiconductor Manufacturing Application -- Chapter 7. A mechanism Design Approach for Decentralized Supply Chain Formation -- Chapter 8. Procurement Network Formation: A Cooperative Game Approach -- Chapter 9. Design Flexible Supply Chain Contracts with Options -- Chapter 10. Build-to-Order Meets Global Sourcing: Planning Challenge for the Auto Industry -- Chapter 11. Practical Modeling in Automotive Production -- Chapter 12. Why is it so Hard to Build and Validate Discrete Event Simulation Models of Manufacturing Facilities? -- Chapter 13. A Practical Approach to Diagnosing and Tuning a Statistical Forecasting System -- Chapter 14. The Ongoing Challenge - Creating an Enterprise-wide Detailed Supply Chain Plan for Semiconductor and Package Operations -- Chapter 15. Production Planning in the Plastics Industry -- Chapter 16. Model Predictive Control in Semiconductor Supply Chain Operations -- Chapter 17. Models and Methods for Production Scheduling in the Pharmaceutical Industry -- Chapter 18. Developing a Computerized Scheduling System for the Steelmaking - Continuous Casting Process -- Chapter 19. A Multi-Model Approach for Production Planning and Scheduling in an Industrial Environment -- Chapter 20. Fuzzy Logic Based Production Scheduling and Rescheduling in the Presence of Uncertainty -- Chapter 21. The Summing-Up.
Electronic reproduction.
Keywords: Business logistics; Economics; Engineering economy; Industrial engineering; Industrial productivity; Inventory control; Operations research; Production planning